Alfabetização científica e protagonismo: relação entre alunos da educação de jovens e adultos e do técnico em açúcar e álcool por meio da educação não formal - Pereira, Adriano Ribeiro (2020)
From Law No. 9394 on, education started to value a more dynamic, multidisciplinary and more applicable teaching in the productive life of the students, so in what determines the Law and looking at the potential of technical course students, the objective of the research was to investigate the scientific literacy (SL) of students of Youth and Adult Education (YAE) through learning situations (LS) designed by students of the Technical Course in Sugar and Alcohol (SAT). Having SASSERON (2008) as a theoretical reference of SL, the students of SAT elaborated six LSs with the purpose of contributing with the SL of chemical and physical transformations together with agroindustrial processes of sugar cane biomass, from a non-formal education. The organization of the six LSs, as well as the SL of SAT students and YAE students were analyzed from the perspective of three axes of literacy, the understanding of scientific terms and concepts, the understanding of the nature of science in investigative, ethical and political facts, and the understanding of the relationship science, technology, society and environment. Besides SL, the research also had the purpose of investigating the "student protagonist" of SAT students. This research had a descriptive character with a qualitative approach to evidence observed through answers to initial and final questionnaires, photos, audio and video recordings and participant observation. The data collection took place at night with 25 students of the 4th module of the SAT course at STS "Bento Carlos Botelho do Amaral" and 17 students of the 3rd grade of YAE High School "Jeremias de Paula Eduardo". The research was divided into stages and modules, the first stage consisted of the modules of motivational mediation, formative and construction/preparation of the LSs and initial data collection with the students of SAT/YAE, while the second stage consisted of the modules of mediation of the SLs of the students of SAT with the students of YAE and final data collection. The results led to evidence that corroborated with the SL of the YAE/SAT students, as well as in the finding of seven student protagonists.